Designing and Developing a Mobile Academic Platform for University - Endariahna Surbakti, Eunike; Adeline Twince Tobing, Fenina; Sasmita Wijaya, Sagita; Rinanda Saputri, Fahmy (International Journal of Science, Technology & Management, 2024)
Academic consultation is a consultation activity between academic supervisors and students in the study and helps solve problems that accept students. The goal is that students who can complete their studies according to their interests and abilities. The implementation of academic consultation is regulated by each study program / faculty / university. The current academic guidance process at Multimedia Nusantara University does not control the students being guided. In addition, the current process of distributing student assistance is done manually by the head and vice of the study program. They divide the average number of students by the number of lecturers. With the random number algorithm, pseudo random number generator will help the division of students with automatic divide. The pseudo random number generator algorithm was chosen because it has the advantage of providing initial value of the process that is produced quickly, simply and saves storage. The design of this online academic consultation application will assist in the academic monitoring process anytime and anywhere. This application developed using flutter and can be use by students and supervisor. The result from this research was application successfully developed and received a score of 88 % for UEQ Questionare, which is categorized as excellent.